Friedenspädagogik und Gewaltfreiheit : Denkanstöße für eine differenzsensible Kommunikations- und Konfliktkultur - Frieters-Reermann, Norbert; Lang-Wojtasik, Gregor (Schriften der Katholischen Hochschule Nordrhein-Westfalen ;, 2015)
Peace has to be learned again and again - and peace education has to deal with the conditions for this in a new way. In this volume, current lines of argumentation of non-violence and peace education are measured in the cpmtext of world society and thus innovative perspectives for peace education in the 21st century are presented.